2015
DOI: 10.1111/andr.12001
|View full text |Cite
|
Sign up to set email alerts
|

Sperm global DNA methylation level: association with semen parameters and genome integrity

Abstract: SUMMARYSperm DNA methylation abnormalities have been detected in oligozoospermic men. However, the association between sperm DNA methylation defects, sperm parameters and sperm DNA, and chromatin integrity remains poorly understood. This study was designed to clarify this issue. We recruited a cohort of 92 men (62 normozoospermic and 30 oligoasthenozoospermic) presenting for infertility evaluation during a 1-year period. Sperm global DNA methylation was evaluated by an ELISA-like method, DNA fragmentation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
78
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 42 publications
15
78
2
3
Order By: Relevance
“…Chromatin Condensation Analysis : Sperm sorted using SPARTAN were subjected to chromatin condensation analysis using the aniline dye blue test (a dye that selectively stains lysine‐rich histone proteins) and compared with sperm sorted by swim‐up and unprocessed semen as previously described 17. Briefly, sperm were washed twice in phosphate‐buffered saline (PBS), treated with 1% sodium dodecyl sulfate in sodium citrate, spread onto a glass slide and allowed to dry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin Condensation Analysis : Sperm sorted using SPARTAN were subjected to chromatin condensation analysis using the aniline dye blue test (a dye that selectively stains lysine‐rich histone proteins) and compared with sperm sorted by swim‐up and unprocessed semen as previously described 17. Briefly, sperm were washed twice in phosphate‐buffered saline (PBS), treated with 1% sodium dodecyl sulfate in sodium citrate, spread onto a glass slide and allowed to dry.…”
Section: Methodsmentioning
confidence: 99%
“…With ICSI, individual sperm are then selected visually based on motility and morphology by a trained embryologist for injection to an egg 7, 8. However, other important sperm attributes that can affect ART outcomes, including sperm DNA–chromatin or chromosomal integrity, mutational, or methylome composition, and the presence of reactive oxygen species (ROS)9, 10, 11, 12, 13, 14, 15, 16, 17 are typically not considered. In particular, long periods of incubation, as well as shear stresses due to centrifugation, increase ROS accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Rodent models showed that exposure to these molecules triggers DNA hypomethylation in sperm along with a dose-dependent drop in sperm counts, impaired testicular histology, reduced sperm production and infertility [29,30] . Interestingly, preliminary observations made in rodents were confirmed in humans since methylation changes in sperm DNA have also been identified in men showing disruptive spermatogenesis and more recently in idiopathic infertility cases [31][32][33][34][35][36][37][38][39][40] . As analyses of DNA methylation pattern in Differentially Methylated Regions (DMRs) of H19 and PEG1/MEST in men with disruptive spermatogenesis clearly showed a link between reduced sperm counts and abnormal methylation [31] , several studies broaden DMRs analysis, including a larger number of genes: IGF2, PEG3, ZAC, LIT1, SNRPN as well as non-imprinted repetitive elements, such as long interspersed nucleotide elements (LINE1) and Alu elements, as surrogates for genomewide DNA methylation changes [33,35] .…”
Section: Consequences Of Changes In Sperm Dna Methylation On Male Fermentioning
confidence: 86%
“…In addition, the research of Montjean et al 22 showed that global DNA methylation in sperm was associated with sperm concentration. Oligozoospermic men had global DNA methylation level which were significantly lower compared to normozoospermic men.…”
Section: Dna Methylation and Male Infertilitymentioning
confidence: 99%